Peningkatan Kemampuan Menulis Teks Laporan Hasil Observasi melalui Model Pembelajaran Berbasis Proyek di Kelas IX-10 SMP Negeri 8 Medan - Saragih, Yesli May Veronika; Ali, Ali; Evita, Evita (Medan Resource Center, 2025)
This study investigates the effectiveness of the project-based learning model in enhancing students' ability to write observational report texts in Class IX-10 at SMP Negeri 8 Medan. The research addresses the problem of students’ low proficiency in composing observational reports that meet structural and linguistic conventions. Employing a Classroom Action Research (CAR) design, the study was conducted over two cycles, each consisting of planning, action, observation, and reflection. Data were gathered through writing tests, classroom observations, and interviews, and analyzed using a combination of descriptive quantitative and qualitative methods. The participants were 29 students (13 males and 16 females). The findings indicate that the implementation of the project-based learning model led to measurable improvements in students’ writing performance. In the first cycle, students demonstrated moderate progress, while the second cycle showed significant gains, with most students surpassing the minimum competency threshold. Students also displayed increased engagement and autonomy in the learning process, alongside enhanced skills in organizing, analyzing, and reporting observations coherently. These results suggest that project-based learning fosters active learning, critical thinking, and sustained motivation, making it an effective pedagogical approach for developing writing skills, particularly in the context of observational report texts.